2022
DOI: 10.4102/sajp.v78i1.1637
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the structure and process of stroke rehabilitation in primary, secondary and tertiary hospitals in Ghana

Abstract: Background: Evidence shows that quality indicators such as the structure and process of stroke rehabilitation can influence patient outcomes. However, not much attention has been paid to the study of these issues in low- and middle-income countries such as Ghana.Objectives: Our study evaluated the structure and process of stroke rehabilitation in primary, secondary and tertiary hospitals in the Greater Accra Region of Ghana.Method: A cross-sectional survey was conducted involving 111 healthcare professionals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Stroke patients in Ghana were reported in this study to be discharged from inpatient rehabilitation within 14 days of admission showing a shorter length of hospital stay. A study conducted in Ghana also reported that stroke patients in Ghana have shorter length of hospital stay (Mohammed, Nyante & Mothabeng 2022). One possible reason for the early discharge could be because of the limitation in bed capacity for stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Stroke patients in Ghana were reported in this study to be discharged from inpatient rehabilitation within 14 days of admission showing a shorter length of hospital stay. A study conducted in Ghana also reported that stroke patients in Ghana have shorter length of hospital stay (Mohammed, Nyante & Mothabeng 2022). One possible reason for the early discharge could be because of the limitation in bed capacity for stroke rehabilitation.…”
Section: Discussionmentioning
confidence: 98%
“…This study aims to provide data to help in better understanding of the structure and process of stroke rehabilitation in Ghana to help in facilitating interventions to improve the quality of stroke rehabilitation, which in turn can improve the outcome of stroke patients. A preliminary study carried out in Ghana to assess the structure and process of stroke rehabilitation in Ghana was conducted by the authors of this study (Mohammed, Nyante & Mothabeng 2022 ) using quantitative methods. In order to have a better understanding of the structure and process of stroke rehabilitation that was recorded in the previous quantitative study, a qualitative study needed to be carried out.…”
Section: Introductionmentioning
confidence: 99%